1982
DOI: 10.1111/j.1600-0447.1982.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment: does the kidney prefer one daily dose instead of two?

Abstract: Renal structure and function were investigated in two groups of long-term lithium treated patients. Lithium was administered in two different ways either in a one-dose per day schedule where the whole dose of lithium was given between 8 and 10 p.m. or in a schedule where the lithium dose was given, divided into two or three doses, during the day. Kidney biopsy was performed, and structural changes in the kidney tissue were determined together with 24-h urine volume in the individual patients. The functional as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 15 publications
4
25
0
2
Order By: Relevance
“…In the largest trial to date, Schou et al 17 found significantly lower urine volumes in the SDD group (2380 mL/24h SDD, compared with 2830 mL/24h MDD, P = 0.05). Similar results were duplicated by both Plenge et al 18 (2250 mL/24h SDD, compared with 4630 mL/24h MDD, P < 0.001) and Bowen et al 19 (1880 mL/24h SDD, compared with 2512 mL/24h MDD, P < 0.05). Authors concluded that less frequent lithium administration was associated with lower urine volumes.…”
Section: Observational Trialssupporting
confidence: 78%
See 3 more Smart Citations
“…In the largest trial to date, Schou et al 17 found significantly lower urine volumes in the SDD group (2380 mL/24h SDD, compared with 2830 mL/24h MDD, P = 0.05). Similar results were duplicated by both Plenge et al 18 (2250 mL/24h SDD, compared with 4630 mL/24h MDD, P < 0.001) and Bowen et al 19 (1880 mL/24h SDD, compared with 2512 mL/24h MDD, P < 0.05). Authors concluded that less frequent lithium administration was associated with lower urine volumes.…”
Section: Observational Trialssupporting
confidence: 78%
“…29 Among the 2 trials that compared renal biopsy results, both found significantly more pathologic damage to the kidneys in patients receiving lithium in MDD. 18,37 In addition to examining renal effects, it is important when proposing a dosage regimen change to also examine other adverse effects and clinical efficacy. Other adverse effects were typically a secondary outcome assessed in these trials, and most found either no difference or a reduction in adverse effects, such as diarrhea, with SDD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another point to keep in mind is that 12 h levels in patients on slow-release lithium are close to peak levels and may be more susceptible to random variation, making laboratory monitoring more diffi cult ( Fig In recent years, clinical practice has also shifted toward a once-daily dosage because most patients tolerate such a regimen well and feel more comfortable. Furthermore, when given in a single daily dose, lithium treatment may be associated with less polyuria and reduced renal concentration capacity (Plenge et al 1982 ;Bowen et al 1991 ). These are important factors leading to better adherence to medication.…”
Section: Pharmacokinetic Properties Of Lithiummentioning
confidence: 97%